Preparation, mechanical, and leaching properties of CaZrO3 ceramic cores. Issue 5 (18th February 2021) - Yang, Zhigang; Li, Kaili; Ma, Shiqing; Yu, Jianbo; Ren, Zhongming
Abstract: The CaZrO3 ceramic core materials with excellent mechanical and chemical properties were successfully prepared using single‐phase CaZrO3 powders. Effects of particle size ratio and sintering temperature on the mechanical and chemical properties of CaZrO3 ceramic core materials were researched. The chemical property was analyzed by leaching research of core materials in 10 wt% and 20 wt% HNO3 solution at the boiling point. Results showed that the suitable particle size ratio was important for the preparation of CaZrO3 ceramic core materials with excellent comprehensive properties. The addition of fine particles in ceramic core materials promoted the densification process owing to the framework formed by coarser particles and sintering neck formed by fine particles between coarse particles, which was beneficial for further improving their bending strength. When the content of particles with 200 mesh size was 80wt%, the highest bending strength was obtained, 54.38 ± 5.28 MPa. The porosity was 17.45% and the volume density was 3.86 g/cm 3 . The increasing sintering temperature increased the densification of CaZrO3 ceramic core materials by offering the sintering driving force, further leading to the improvement of bending strength. When the temperature was 1650℃, at the 20% content of particles with 200 mesh size, the highest bending strength of CaZrO3 cores reached 51.01 ± 5.18 MPa. Meanwhile, the porosity was 18.65% and the volume density was 3.83 g/cm 3 . Additionally, the CaZrO3 samples could be effectively leached in 10 wt% HNO3 solution. Therefore, CaZrO3 materials with good mechanical and leaching properties were believed to be a suitable candidate for ceramic core materials in the investment casting of alloys with high melting point.